2014
DOI: 10.1002/adhm.201400084
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Healing of Acrylic Bone Cement

Abstract: Self-healing in orthopedic bone cement is demonstrated with a novel thermoplastic solvent-bonding approach. Low toxicity solvent-filled microcapsules, embedded in a commercial acrylic bone cement matrix, enable recovery of up to 80% of the virgin fracture toughness of the cement at room and body temperature conditions without external stimuli or human intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…A good solvent is one for which the interactions between the polymer segments and solvent molecules are more energetically favorable than those between the polymer segments themselves and is usually identified as one whose solubility parameter (d) is close to that of the polymer [29,33]. Good solvents for PMMA include ethyl phenylacetate (EPA), phenylacetate (PA), chlorobenzene (PhCl) and anisole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A good solvent is one for which the interactions between the polymer segments and solvent molecules are more energetically favorable than those between the polymer segments themselves and is usually identified as one whose solubility parameter (d) is close to that of the polymer [29,33]. Good solvents for PMMA include ethyl phenylacetate (EPA), phenylacetate (PA), chlorobenzene (PhCl) and anisole.…”
Section: Introductionmentioning
confidence: 99%
“…Good solvents for PMMA include ethyl phenylacetate (EPA), phenylacetate (PA), chlorobenzene (PhCl) and anisole. Gladman et al have recently demonstrated autonomous solvent healing in a bone cement thermoplastic system containing microcapsules with a liquid PMMA-anisole core material [33]. PMMA was added to the core solvent (anisole) to promote increased healing efficiency in small scale cracks within the bone cement system and to promote environmental stability of the microcapsules [33].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, these systems need additional healing agents to enable self‐healing. The most common strategy toward design of extrinsic self‐healing biomaterials was pioneered by White and co‐workers and entails the incorporation of capsules containing healing liquids into a non‐self‐healing matrix ( Figure ). In these biomaterials, mechanical damage induces rupture of the capsules and release of their cargo into microcracks to enable self‐healing.…”
Section: Extrinsic Self‐healing Biomaterialsmentioning
confidence: 99%
“…As mentioned above, the surface of the glass particles is coated with a silane coupling agent such as 3‐(triethoxysilyl)propyl methacrylate to improve the mechanical properties of resin‐based dental composites by forming covalent bonds between the glass surface and the resin matrix. [15a,17,18]…”
Section: Extrinsic Self‐healing Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation